To determine which step contains an error in using the Commutative Property of Addition, we should review each step carefully.
Step 1: \[ 8 + 4 + x^2 - x^2 + 17x = 10 + 2 + 10x - 4x^2 + 4x^2 \]
This step rearranges the terms on both sides. However, both sides should add up correctly:
- Left: \(8 + 4 + 17x + x^2 - x^2 = 12 + 17x\)
- Right: \(10 + 2 + 10x - 4x^2 + 4x^2 = 12 + 10x\)
Step 1 does not equal.
Step 2: Rearranged the equation from Step 1: \[ 8 + 4 + 17x + x^2 - x^2 = 10 + 2 + 4x^2 - 4x^2 + 10x + 7x \]
When checking this step:
- Left: \(12 + 17x + 0 = 12 + 17x\)
- Right: \(12 + 10x + 7x + 0 = 12 + 17x\)
Step 2 is right.
Step 3: This reads: \[ 12 + 17x + x^2 = 12 - x^2 + 17x \]
On evaluating:
- Left: \(12 + 17x + 0 = 12 + 17x\)
- Right has an \( -x^2\) on the right that was not accounted for in the left.
This equation is incorrect because there is a difference in the signs regarding \(x^2\).
Thus, the error occurred in Step 3.
The answer is Step 3.